Beginning to See the Light: Lessons Learned From the Development of the Circadian System for Optimizing Light Conditions in the Neonatal Intensive Care Unit - Hazelhoff, Esther M.; Dudink, Jeroen; Meijer, Johanna H.; Kervezee, Laura (Frontiers in Neuroscience, 2021)
The circadian timing system optimizes health by temporally coordinating behavior and physiology. During mammalian gestation, fetal circadian rhythms are synchronized by the daily fluctuations in maternal body temperature, hormones, and nutrients. Circadian disruption during pregnancy is associated with negative effects on developmental outcomes in the offspring, highlighting the importance of regular and robust 24-h rhythms over gestation. In the case of preterm birth (before 37 weeks of gestation), maternal cues no longer synchronize the neonate’s circadian system, which may adversely affect the neonate. There is increasing evidence that introducing robust light-dark cycles in the Neonatal Intensive Care Unit has beneficial effects on clinical outcomes in preterm infants, such as weight gain and hospitalization time, compared to infants exposed to constant light or constant near-darkness. However, the biological basis for these effects and the relationship with the functional and anatomical development of the circadian system is not fully understood. In this review, we provide a concise overview of the effects of light-dark cycles on clinical outcomes of preterm neonates in the NICU and its alignment with the development of the circadian system.